1994
DOI: 10.1007/bf02270499
|View full text |Cite
|
Sign up to set email alerts
|

The upper portion of the Japan Sea Proper Water; Its source and circulation as deduced from isopycnal analysis

Abstract: All of the available hydrographic station data (temperature, salinity, dissolved oxygen, phosphate and nitrate) taken in various seasons from 1964 to 1985 are analyzed to show where the upper portion of the Japan Sea Proper Water (UJSPW) is formed and how it circulates. From vertical distributions of water properties, the Japan Sea Proper Water can be divided into an upper portion and a deep water at the σ 1 (potential density referred to 1000 db) depth of 32.05 kg m -3 surface. The UJSPW in the north of 40°N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 10 publications
3
46
0
2
Order By: Relevance
“…As discussed in Senjyu and Sudo (1994), Area I (inset of Fig. 1) includes the UJSPW formation region and Area III is the farthest reaching area of the UJSPW.…”
Section: Datamentioning
confidence: 93%
See 1 more Smart Citation
“…As discussed in Senjyu and Sudo (1994), Area I (inset of Fig. 1) includes the UJSPW formation region and Area III is the farthest reaching area of the UJSPW.…”
Section: Datamentioning
confidence: 93%
“…1) and finally flows into the Yamato Basin. Further, Senjyu and Sudo (1994) showed that AOU (Apparent Oxygen Utilization) and phosphate contents in the northwestern area including the UJSPW formation region (Area I in inset of Fig. 1) are in wider ranges than those in the region west of the Yamato Rise (Area II) and on the Yamato Basin (Area III); this suggests that the water characteristics of the UJSPW must be subject to a year-to-year variation.…”
Section: Introductionmentioning
confidence: 97%
“…Between these first two regions is a boundary zone termed the ''subpolar front'' which is formed at around 40 N. The third region is the deep region, and includes the layer below approximately 500 m in depth occupied by deep water termed the Japan Sea Proper Water, which is thought to be formed by strong deep convection in the winter in the northwestern part of the Japan Sea. 8,9) The Japan Sea Proper Water and the materials dissolved or suspended therein are trapped in the enclosed bottom topography of the Japan Sea, which has a turnover time of about 100 years. 10) Although several monitoring operations in the Japan Sea have yielded a significant amount of data on anthropogenic radionuclides, most of the works were carried out in the Exclusive Economic Zone (EEZ) of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Using all historical data, Senjyu and Sudo [1994] conclude that UJSPW is formed by wintertime convection in the region west of 136.0øE, between 40.0 ø and 43.0øN, in one of the possible regions suggested by Sudo [1986] and that it flows cyclonically along the bottom topography of the Japan Basin. The formation region suggested by Senjyu and Sudo [1994] experiences a large air-sea heat flux caused by strong seasonal winds, which are enhanced by topographic effects [Kawamura and Wu, 1998], supporting the possibility of wintertime convection in this region.…”
Section: Introductionmentioning
confidence: 93%